Input shaping and PID controller for rotary crane - Enti Nashila, Riazuddin (2012)
The rotary cranes are widely used in common industrial structures such as construction sites and automotive tracks to transfer loads and materials. The rotary crane controlling process is difficult without method because the motion expected to be faster. One of the current problems in industry and building construction is that rotary cranes became larger and higher. So they need to be faster to achieve acceptable transfer times. But unfortunately, rotary cranes with large structures that are moving at high speed are always associated undesirable payload oscillations resulting from the system dynamics. The purpose of controlling the rotary crane is transporting the load faster without causing any excessive swing at the final position. Rotary cranes have very strong structures in order to lift heavy payloads. The oscillations of the loads must be reduced to prevent hazards for people and equipment in the work place. In this work, two types of controllers are studied which is input shaping and PID controller. The input shaping controller and PID controller is developed to control the horizontal motion of pendulum and arm position in rotary cranes to reduce the sway angle of the rope to its set point during the transportation process and time response specification. It is developed to control the sway of load to correcting the radial and rotational motion of cranes and the oscillation damping PID controllers for damping the oscillation angles of the loads. LabVIEW and MATLAB software was used to develop input shaping and Proportional Integral Derivative (PID) controller and to simulate the system response. The simulation results demonstrate the effectiveness of the proposed method.